Conformational and structural analysis of 2-allyl-1,2-benzisothiazol-3(2H)-one 1,1-dioxide as probed by matrix-isolation spectroscopy and quantum chemical calculations - Gómez-Zavaglia, Andrea (2009)
http://www.sciencedirect.com/science/article/B6TGS-4THC1JN-1/2/1228ea86baa026383b4037e881569263